Australia and its Importance in the World Economy - Syrvatková, Radka (2009)
The aim of my thesis is to analyze Australia's political and economic situation. My thesis consists of two parts. In the first part I describe Australia in terms of geography, and I acquaint readers with its history, especially after World War II. In the second part I deal with the current economic situation of Australia, and political system which I compare to the political system in Great Britain within the Commonwealth. In conclusion, I summarize my work and find out Australia's future strengths, weaknesses, opportunities, and threats using SWOT analysis.